Morphological measurements of common voles, Microtus arvalis - Searle, Jeremy; Martínková, Natália; Barnett, Ross; Cucchi, Thomas; Struchen, Rahel; Pascal, Marine; Pascal, Michel; Fischer, Martin; Higham, Thomas; Brace, Selina; Ho, Simon; Quere, Jean-Pierre; et al. (Dryad Digital Repository, 2013)
Morphological coordinates collected from 2D images of common vole skulls. Raw cartesian coordinates in pixels are given in columns Rawx1, Rawy1 through to Rawx30, Rawy30. Columns with respective names starting with Ali are Proscrustes coordinates; the shape variables after the Procrustes superimposition. Samples are labelled with the population code and number from the individual voucher.